Multi-Agent Systems Control Spectrum - Shikhin, Vladimir (IntechOpen, 2019)
This book integrates the practices of enthusiastic investigators in the field of MAS-based approaches, elaboration, and implementation. The content of the book identifies the most complicated tasks and their possible solutions while implementing MAS instrumentation into engineering practice. The proposed focus on the control problems involves a wide range of adjacent problems described in the chapters of the book. Material presented in the book aim to provide the basic knowledge for further MAS-systems study and control design to reach the goals and needs coming from engineering practice under often contradictory existing requirements.